2022
DOI: 10.18521/ktd.1165651
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Serum Folate-Receptor-1 Levels in Patients with Non-Small Cell Lung Cancer

Abstract: Objective: Histopathological overexpression of folate receptor-1 (FOLR1) involved in folate transport in cell growth has been reported in various cancers. Increased serum FOLR1(sFOLR1) has also been reported in epithelial ovarian cancer. The aim was to investigate sFOLR1 levels in non-small cell lung cancer (NSCLC) patients and the response prediction of the standard chemotherapy targeting folic acid metabolism. Method: In this prospective study, sFOLR1 levels were investigated in 30 healthy individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For example, in a recent study, the lower levels of FRs found in the plasma of ovarian cancer patients were 6.25 and 3.125 ng/mL, respectively [10]. In another recent study, the level of FRs in the serum of lung cancer patients was 0.4 ng /mL [11]. In addition, the migration of cancer cells into the circulatory system was observed in the metastasis stage of cancer, supporting the use of body fluids for cancer detection and their evolution during therapy [12].…”
Section: Introductionmentioning
confidence: 91%
“…For example, in a recent study, the lower levels of FRs found in the plasma of ovarian cancer patients were 6.25 and 3.125 ng/mL, respectively [10]. In another recent study, the level of FRs in the serum of lung cancer patients was 0.4 ng /mL [11]. In addition, the migration of cancer cells into the circulatory system was observed in the metastasis stage of cancer, supporting the use of body fluids for cancer detection and their evolution during therapy [12].…”
Section: Introductionmentioning
confidence: 91%